2013
DOI: 10.1302/0301-620x.95b11.32904
|View full text |Cite
|
Sign up to set email alerts
|

Reducing blood loss after total knee replacement

Abstract: Blood loss during total knee replacement (TKR) remains a significant concern. In this study, 114 patients underwent TKR, and were divided into two groups based on whether they received a new generation fibrin sealant intra-operatively, or a local infiltration containing adrenaline. Groups were then compared for mean calculated total blood volume (TBV) loss, transfusion rates, and knee range of movement. Mean TBV loss was similar between groups: fibrin sealant mean was 705 ml (281 to 1744), local adrenaline mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
6
0
4
Order By: Relevance
“…Reinhardt et al 13 observed that the total blood loss was similar in a retrospective cohort of 114 patients submitted to TKA, in which 1 group received the topical fibrin sealant (Evicel), and another group was submitted to a local infiltration containing epinephrine. Considering that local periarticular epinephrine injection reduces bleeding rates after TKA, the use of fibrin sealant may be considered effective.…”
Section: Discussionmentioning
confidence: 97%
“…Reinhardt et al 13 observed that the total blood loss was similar in a retrospective cohort of 114 patients submitted to TKA, in which 1 group received the topical fibrin sealant (Evicel), and another group was submitted to a local infiltration containing epinephrine. Considering that local periarticular epinephrine injection reduces bleeding rates after TKA, the use of fibrin sealant may be considered effective.…”
Section: Discussionmentioning
confidence: 97%
“…Od krycie cho rób prze no szo nych przez krew zwró ci ło większą uwa gę na po wi kła nia trans fu zji, po pu la ry zu jąc me to dy al ter na tyw ne [6,18]. Część z nich zo sta ła dokład nie zwe ry fi ko wana [4,10,[14][15][16][17][18][19]. Au to trans fu zja krwi po bie ra nej przed za bie giem, po mi mo efek tywno ści wy ma ga wcze śniej sze go za pla no wa nia i czę sto po ope ra cji oka zu je się zbęd na [18,20,21].…”
Section: Discussionunclassified
“…The discovery of blood-borne diseases drew more attention to complications of blood transfusion and the popularity of alternative methods grew [6,18]. Some of those alternative solutions have been thorou ghly verified [4,10,[14][15][16][17][18][19]. Auto transfu sion of blood collected from the patient before sur gery, although effective, requires prior plan ning and, after surgery, it often turns out to be unne ces sary [18,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Despite that advancements in fixation and design techniques of implants have substantially increased functional results and survival rates of total knee arthroplasty (TKA), during the procedure loss of blood is a major concern that is perioperatively estimated to be 850-1600 mL [1]. During TKA, Patient's recovery may be affected negatively by blood loss.…”
Section: Introductionmentioning
confidence: 99%